Double‐blind, randomised, placebo‐controlled trial on the effect of L‐carnitine and L‐acetylcarnitine on sperm parameters in men with idiopathic oligoasthenozoospermia. (15th March 2019) - Micic, Sava; Lalic, Natasa; Djordjevic, Dejan; Bojanic, Nebojsa; Bogavac‐Stanojevic, Natasa; Busetto, Gian Maria; Virmani, Ashraf; Agarwal, Ashok
Abstract: Carnitine is essential for energy metabolism and spermatozoa maturation. Combining L‐carnitine and L‐acetylcarnitine with micronutrients has been investigated as a treatment for infertility in men. We evaluated the effects of a therapeutic formulation, Proxeed Plus, on sperm parameters in oligoasthenozoospermic men. This prospective, randomised, double‐blind, placebo‐controlled clinical trial involved 175 males (19–44 years) with idiopathic oligoasthenozoospermia who failed to impregnate their partners (12 months). Males received Proxeed Plus or placebo for 3 and 6 months. Sperm volume, progressive motility and vitality significantly ( p  < 0.001) improved after 6 months compared to baseline. Sperm DNA fragmentation index significantly decreased compared to baseline ( p  < 0.001) and the 3‐month therapy ( p  = 0.014) in treated men. Increased seminal carnitine and α‐glucosidase concentration also positively correlated with improved progressive motility. Decreased DNA fragmentation index was the good predictor of progressive sperm motility >10%, and simultaneous measurement of changes in sperm vitality and DNA fragmentation index gave the highest probability of sperm motility 10% (AUC = 0.924; 95% CI = 0.852–0.996; p  < 0.001). Logistic regression analyses revealed DNA fragmentation index decrease as the only independent predictor of sperm motility 10% (OR = 1.106; p  = 0.034). We have demonstrated the beneficial effects of carnitine derivatives on progressive motility, vitality and sperm DNA fragmentation. Combining metabolic and micronutritive factors is beneficial for male infertility.